Politik Hukum Sistem Pemilihan Umum Presiden dan Wakil Presiden dalam Perspektif Pancasila - Adnan Taufiq; Didik Suhariyanto; Ismail (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The research objectives in this thesis are based on the two problem formulations raised, namely as follows: To find out and study the Presidential and Vice Presidential Election system based on Law Number 7 of 2017 concerning General Elections. To find out and study the Legal Politics of the President and Vice President in Indonesia based on Law Number 7 of 2017 concerning General Elections, viewed from the Pancasila Perspective. The research method used is normative juridical legal research. The results of the research and discussion are as follows: First, the direct and indirect Presidential election system emerged due to a misinterpretation of the 4th principle of Pancasila which reads